2019
DOI: 10.18176/jiaci.0323
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategy According to Differences in Response to Omalizumab in Patients With Chronic Spontaneous Urticaria

Abstract: Chronic spontaneous urticaria (CSU) is a heterogeneous condition that can severely impact quality of life, which is why rapid disease control is essential. Symptomatic first-line treatment of CSU is the licensed dose of second-generation H1 antihistamines. For second-line treatment, this dose may be increased by up to four times. In patients who fail to respond to these higher doses of H1 antihistamines, treatment with omalizumab (up to 24 weeks) is recommended to achieve disease control. After this 24-week pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Chronic spontaneous urticaria (CSU), a subgroup of chronic urticaria, is defined as the spontaneous daily, or almost daily, occurrence of itchy hives (wheals), angioedema, or both, lasting for 6 weeks or more, with no apparent external trigger [ 1 ]. CSU presents a major burden of disease for patients and society with a significantly diminished quality of life [ 2 , 3 ]. The estimated lifetime point prevalence of CSU is approximately 0.5–1% and nearly 60% of patients with CSU continue to have the disease despite treatment with antihistamines at the licensed dose [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic spontaneous urticaria (CSU), a subgroup of chronic urticaria, is defined as the spontaneous daily, or almost daily, occurrence of itchy hives (wheals), angioedema, or both, lasting for 6 weeks or more, with no apparent external trigger [ 1 ]. CSU presents a major burden of disease for patients and society with a significantly diminished quality of life [ 2 , 3 ]. The estimated lifetime point prevalence of CSU is approximately 0.5–1% and nearly 60% of patients with CSU continue to have the disease despite treatment with antihistamines at the licensed dose [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown examples of the optimization of omalizumab treatment in patients who show inadequate response by increasing the dose or decreasing the dosing intervals [ 27 ]; a more flexible treatment regimen rather than a constant regimen including shortening dosing interval or augmenting dose based on the patient’s symptoms is also likely to provide better symptom control [ 28 , 29 ]. Although there is currently no algorithm for the individualized management of omalizumab treatment that is agreed on, treatment algorithms based on specific response profiles of patients refractory to AHs have been proposed to facilitate clinical management of omalizumab and enable clinicians to assess therapeutic strategy [ 2 , 30 , 31 ]. The aim of this article is to provide a summary of the published real-world evidences for the updosing of omalizumab in the treatment of CSU.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that 34% of physicians discontinued OMA, 32% extended the interval and 4.2% reduced the dose after obtaining complete response. Other reports have also suggested the dose reduction or the interval extension of OMA after achieving relief of urticarial symptoms 17–20 . These dose reductions, interval extensions and discontinuation of OMA mainly contribute to reduce economic burden on patients and society.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to binding to serum IgE which results in a decrease of total and autoantigen-specific IgE levels, other potential mechanisms of action to explain OMA efficacy in CSU have been proposed 15 ( Table 1 ).…”
Section: Therapeutics and Integral Management Of Chronic Spontaneous Urticaria And Chronic Inducible Urticariamentioning
confidence: 99%